Implementation Of An Internet Of Things-Based Motorcycle Security System Using GPS Tracker And Microcontroller - Ahmad Ferdian Syaputra; Adi Wibowo Adi (CV. AFDIFAL MAJU BERKAH, 2026)
Motor vehicle theft remains a common problem caused by the weakness of conventional security systems that rely solely on mechanical locks. This study aims to design and implement an Internet of Things (IoT)-based motorcycle security system using ESP32 integrated with RFID RC522, GPS Neo-6M, vibration sensor, starter relay, buzzer, ThingsBoard Cloud, and Telegram Bot. The research employed an experimental method with a prototype approach, including requirement analysis, system design, hardware and software implementation, system integration, and system testing. The developed system performs user authentication using RFID, detects vehicle vibrations, transmits real-time vehicle location coordinates, and provides security notifications through Telegram. Vehicle telemetry data are also transmitted to the ThingsBoard Cloud platform using the MQTT protocol for real-time monitoring. The testing results indicate that all system features functioned properly, including RFID authentication, GPS monitoring, vehicle relay control, vibration detection, MQTT data transmission, and Telegram notifications, with a system success rate of 100%. The developed IoT-based vehicle security system is capable of improving vehicle security more effectively and modernly compared to conventional security systems.